The effect of creep damage formulation on crack tip fields, creep stress intensity factor and crack growth assessments (Fracture and Structural Integrity, 2017)
Fields of stress, strain rate and process zone of a mode I creep crack growth are analyzed by employing damage evolution equations. Damage models for fracture of process zone represented by stress based formulation. Two expressions are presented to describe the stress-sensitive nature of multiaxial rupture behavior. Both damage free and defective creeping solids have been studied. The variation of creep stress and the crack-tip governing parameter in the form of creep In-integral with time and the evolution of creep damage were analyzed by using the FE-model. The effect of the introduced creep stress intensity factor as a function of creep time through the continuum damage mechanics of the creep crack growth are discussed in detail.
Keywords: Creep damage; Creep SIF; Multi-axial stress function